2022
DOI: 10.1681/asn.2021020182
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Visualization of the Podocyte Actin Network Using Integrated Membrane Extraction, Electron Microscopy, and Machine Learning

Abstract: Background Actin stress fibers are abundant in cultured cells, but little is known about them in vivo. In podocytes, much evidence suggests that mechanobiologic mechanisms underlie podocyte shape and adhesion in health and in injury, with structural changes to actin stress fibers potentially responsible for pathologic changes to cell morphology. However, this hypothesis is difficult to rigorously test in vivo due to challenges with visualization. A technology to image the actin cytoskeleton at high resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…However, increased dynamic motility could destabilize this state upon exposure to adriamycin-induced injury [ 45 ]. Moreover, the well-formed configuration of foot processes is contingent upon the soundness of the actin cytoskeleton, and the obliteration of podocytes emanates from the vulnerable cytoskeleton due to the loss of filamentous actin [ 46 ]. Previous studies have shown CK yields renoprotective effects in a dose-dependent manner, with the most significant improvements observed at a dosage of 40 mg/kg, alongside its anti-inflammatory actions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, increased dynamic motility could destabilize this state upon exposure to adriamycin-induced injury [ 45 ]. Moreover, the well-formed configuration of foot processes is contingent upon the soundness of the actin cytoskeleton, and the obliteration of podocytes emanates from the vulnerable cytoskeleton due to the loss of filamentous actin [ 46 ]. Previous studies have shown CK yields renoprotective effects in a dose-dependent manner, with the most significant improvements observed at a dosage of 40 mg/kg, alongside its anti-inflammatory actions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reorganization of the actin cytoskeleton and of cell-matrix adhesions towards a contractile and mechanically enforced RhoA-dependent actomyosin cytoskeleton is a common pattern in podocytopathy and considered a driving factor of glomerular disease [ 9 , 12 , 19 , 62 ]. Analysis in human kidney tissue showed increased ARHGAP29 expression in early glomerular disease stages ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanical forces can also influence the assembly and disassembly of AFs [ 10 ]. The actin cytoskeleton is strongly sensitive and responsive to the mechanical stress that podocytes face [ 20 ]. The AFs provide a structural and functional basis, thus building the cytoarchitecture of podocytes and enhancing adhesion to the extracellular matrix [ 7 , 16 ].…”
Section: Composition and Structure Of The Podocyte Cytoskeletonmentioning
confidence: 99%